Study on the Design of Avocado-fiber Skincare Knitted Underwear - Wang Shi; Li Junjia; Zhao Fu (E3S Web of Conferences, 2021)
With the continuous changes taken place in people’s lifestyles, functional underwear has drawn attention from more consumer groups. Skincare, comfortable knitted underwear fabrics can be made by adding refined avocado oil into viscose to yield fibers and then blending it with other fibers such as acrylic and wormwood fiber. This article first introduces the moisture-retaining principles, raw material selection, and skincare property of avocado-fiber knitted fabric, and discusses the comfortability of the fabric, the requirements of underwear fitness, the style design optimization, and the functional area partitioning, aiming to provide design ideas for the development of the new skincare functional knitted underwear.